(untitled) (Journal of Imam Al-Kadhim College, 2025)
This study determined the threshold for starting the narrative in the first person in the stories of “Ismail Sakran” especially the dominant text strip in his stories, to be able to begin in general with the basic elements in writing short stories. Because of its effect in promoting the narrative plot, and is supported by the imaginative world of the story, and because of its effective influence on the reader through his suspense, attraction, arousing his curiosity, and creating tension to continue reading the text.